2021
DOI: 10.1142/s2301385022300013
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Reconfigurable Drones: Classification, Characteristics, Design and Control Technologies

Abstract: Recently, reconfigurable drones have gained particular attention in the field of automation and flying robots. Unlike the conventional drones, they are characterized by a variable mechanical structure in flight, geometric adaptability, aerial reconfiguration, high number of actuators and control inputs, and variable mathematical model. In addition, they are exploited to flight in more cluttered environments, avoid collisions with obstacles, transport and grab objects, cross narrow and small spaces, decrease di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 132 publications
0
12
0
Order By: Relevance
“…Furthermore, they can negotiate narrow gaps, fly in crowded environments, inspect sensitive locations, and transport multiple objects without auxiliary manipulator's arms. 1 According to recent studies, [1][2][3] the reconfigurable multirotors can be divided as shown in Figure 1. In the paper, 4 a new reconfigurable quadcopter, which can change its mechanical structure, was presented.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they can negotiate narrow gaps, fly in crowded environments, inspect sensitive locations, and transport multiple objects without auxiliary manipulator's arms. 1 According to recent studies, [1][2][3] the reconfigurable multirotors can be divided as shown in Figure 1. In the paper, 4 a new reconfigurable quadcopter, which can change its mechanical structure, was presented.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, they can negotiate narrow gaps, fly in crowded environments, inspect sensitive locations, and transport multiple objects without auxiliary manipulator’s arms. 1…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During these last years, reconfigurable UAVs have occupied a prominent place in the domain of flying systems and robotics. These new drones can eliminate several problems encountered in the conventional UAVs such as, the flying in congested areas, building inspection, fixed mechanical structure, design complexity, energy consumption, fault tolerant control and obstacles avoidance [1][2][3][4][5]. They are a promising solution in the near future due to their shape characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…They are a promising solution in the near future due to their shape characteristics. They allow increasing considerably the capabilities and performance of classical drones in terms of multi-functionalities using variable structure, geometric adaptation, surfaces inspection, energy consumption by exploiting the change of their morphology, maneuverability, obstacles avoidance and fault tolerant control using their high agility [5][6][7].…”
Section: Related Workmentioning
confidence: 99%